2006
DOI: 10.1007/s10209-006-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and non-use: views of older users

Abstract: This paper reports the results of two connected surveys of computer and Internet use among the older population in the UK. 120 questionnaires and interviews were completed with participants aged over 55 in Derbyshire and 353 questionnaires and interviews with over 50s in Scotland. Rates of use, computer and Internet activities, and reasons for use and non-use were investigated. These were backed up by four semistructured interviews with IT trainers, describing experiences and issues of training this age group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
126
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 17 publications
5
126
1
3
Order By: Relevance
“…Second, there has been a negative image of the elderly since the early 21 th century, due to their lack of productivity and loss of social prestige (Dias, 2012). Additionally, many studies on the digital divide report a strong negative correlation between age and technology adoption and use (e.g., Czaja and Lee, 2007;Morris, Goodman, and Brading, 2007;Neves and Amaro, 2012;van Deursen and van Dijk, 2014), which further devalues the older adult group. However, this situation is gradually being inverted and older adults are gaining more attention in academic, business and technology industry worlds for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there has been a negative image of the elderly since the early 21 th century, due to their lack of productivity and loss of social prestige (Dias, 2012). Additionally, many studies on the digital divide report a strong negative correlation between age and technology adoption and use (e.g., Czaja and Lee, 2007;Morris, Goodman, and Brading, 2007;Neves and Amaro, 2012;van Deursen and van Dijk, 2014), which further devalues the older adult group. However, this situation is gradually being inverted and older adults are gaining more attention in academic, business and technology industry worlds for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the older adults of today have different values, attitudes, life expectancy, life styles and financial possessions from those of previous generations and therefore our knowledge about older adults needs to be updated (Ahmad, 2002). Moreover, a number of studies present evidence that older adults are just as likely as anybody else to accept and adopt technology (e.g., Conci et al, 2009;Mallenius, Rossi, and Tuunainen, 2007;Morris et al, 2007;Rogers, Mayhom, and Fisk, 2009;Rogers and Mynatt, 2003;Selwyn, 2004;Steele, Secomble, and Wong, 2009;Vuori and Holmlund-Rytkönen, 2005), so it is unfair to consider them technophobic. Older adults' expectations of mobile communications are not very different from those of generic users, namely reliable personal communications and services to improve safety and quality of life (Swindell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Venkatesh, V.; Morris;Davis;Davis (2003). User acceptance of information technology: Toward a unified view.…”
Section: Resultsmentioning
confidence: 99%
“…Peacock and Kunemund (2007) note that "lack of a device, motivational indifference and deficient knowledge are the main reasons behind non-usage of the Internet by seniors" (p. 198). Similarly, Morris, Goodman and Brading (2007) found that seniors were unaware of the Internet, were afraid to use it, or felt that they were getting too old to be bothered with the technology. Regardless, research has been done that looks at how to meet seniors information needs in the changing digital environment (Godfrey & Johnson, 2009;Campbel, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There seems to be consensus among researchers that while the uptake of ICTs among citizens in the EU and the U.S. is increasing, older persons are much less likely to be online or have broadband access than younger people and that this divide will continue for the foreseeable future (Morris, Goodman & Brading, 2007 The reasons advanced for the above low statistics include lack of interest, feeling too old, fear of technology compounded by rapid hardware and software development, lack of ICT skills and experience, age-related functional restrictions, and the cost of acquiring and maintaining computers and Internet connection (Morris, Goodman & Brading, 2007). Seniors are also more likely than any other age group to be living with some kind of disability, which could hinder their capacity to get to a computer training center or read the small type on many Web sites (Fox, 2004).…”
Section: Age and Digital Exclusionmentioning
confidence: 99%